Inter-confessional relations in Iran and their influence on the situation in the region - N.M. Mamedova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper is devoted to the analysis of different faiths in Iran and to the official national policy. These problems are extremely important for Iran, because religious controversies are associated with national and religious contradictions there. We believe that the official national and religious policy has an impact on Iran's policy in the region where “separated peoples” live along the borders of the country. The statistical demographic data and economic potential of the region have been analyzed, and it has been revealed that the most economically backward provinces are inhabited by ethnic minorities. These provinces are the main hotbeds of socio-political instability and separatists movements. The Islamic leadership policy in recent years, which has been focused on maintaining the living standards in the backward provinces attracting budgetary and Islamic funds, has been considered. It has been concluded that geopolitical factors and the influence of the “third forces” are responsible for the strengthening of instability in the region and for fanning Sunni-Shia antagonism. Their role is much more important than the existing religious controversies. The main aim for the Iranian leadership is to preserve the national integrity of the country, to fight against separatist movements and to prevent attempts to create the “Greater Middle East”. The official national and religious policy is in line with these aims.